Chemical Composition and Antioxidant Activity of Two Edible Mycorrhizal Fungi from South China - Chen, X.h.; Zhou, H.B.; Qiu, G.Z. (Asian Journal of Chemistry, 2010)
Two wild edible mycorrhizal fungi (Russula virescens and Cantharellus cibarius) from South China were analyzed for the chemical composition and antioxidant activity. The two mushrooms proved to have antioxidant potential, using reducing power, chelating effect on ferrous ions, scavenging effect on hydroxyl free radicals and 2,2-diphenly-1-picrylhydrazyl (DPPH) radical scavenging method. Both species contained very useful phytochemicals such as phenolics, flavonoids and b-carotene. The combination of bioactive substances and rich nutritional composition (high contents in protein and carbohydrates, low content in fat) in the two wild mushrooms should be useful to consu-mers in encouraging them to utilize the nutritive potential of the wildly growing edible mushrooms.